Global, regional, and national burden of hip dislocation, 1990–2021, and Bayesian age-period-cohort predictions: Systematic analysis of the Global Burden of Disease study, 2021 - Shun Lin; Xiu Yang; Baorong Cai; Jie Xiao; Qiping Wu; Guanyuan Yi; Xuesong Han; Feng Shen (PLoS ONE, 2026)
Background Hip dislocation is a severe, clinically rare trauma. The global incidence, trends, and causes of hip dislocation have not been precisely documented. We aimed to explore the burden of hip dislocation from 1990 to 2021 and predict the trends over the next two decades. Methods Data from the Global Burden of Disease (GBD) Study 2021 were used to describe the incidence, years lived with disability (YLD), and the corresponding age-standardized rates (ASRs) of hip dislocation for 1990 and 2021, stratified by sex, age, and the Socio-Demographic Index (SDI) across 21 GBD regions and 204 countries and territories. Joinpoint regression analysis was employed to investigate the temporal trends in incidence. Correlations between ASRs and SDI at the regional and national levels were assessed using Pearson correlation analysis. A Bayesian Age-Period-Cohort (BAPC) model was constructed to predict the disease burden for hip dislocation for the next 20 years. Results In 2021, 2,429,935 new cases (95% uncertainty interval [UI] 1,634,456–3,549,251) of hip dislocation were recorded globally, with 109,146 YLDs (95% UI 57,181–190,161) attributable to hip dislocation. Between 1990 and 2021, the incidence of hip dislocation increased by 18.4% (95% UI 8.5–30.5%) and the YLDs increased by 57.2% (95% UI 50.9–66.4%). The corresponding average annual percentage changes (AAPC) in the age-standardized incidence rate and YLD were −0.712 (95% UI −0.79 to −0.634) and −0.535 (95% UI −0.59 to −0.481), respectively. The highest disease burden occurred in regions with high-SDI. Yemen and Afghanistan had the highest age-standardized incidence rates (ASIRs). At both regional and national levels, statistically significant non-linear relationships were observed between the ASRs of hip dislocation and SDI. The highest incidence occurred in young adulthood for males and old age for females. The leading cause was falls. The BAPC model predicts an increasing burden of hip dislocation among females over the next 20 years. Conclusion The global burden of hip dislocation has increased over the last three decades, and is relatively larger in some high-SDI regions and low-income countries. The burden of hip dislocation is expected to increase, particularly among elderly females, due to population aging. Therefore‌, appropriate preventive measures should be developed to mitigate this trend.